3D Printed Silicones with Shape Memory - Amanda S. Wu (Nature Portfolio, 2017)
Abstract Direct ink writing enables the layer-by-layer manufacture of ordered, porous structures whose mechanical behavior is driven by architecture and material properties. Here, we incorporate two different gas filled microsphere pore formers to evaluate the effect of shell stiffness and Tg on compressive behavior and compression set in siloxane matrix printed structures. The lower Tg microsphere structures exhibit substantial compression set when heated near and above Tg, with full structural recovery upon reheating without constraint. By contrast, the higher Tg microsphere structures exhibit reduced compression set with no recovery upon reheating. Aside from their role in tuning the mechanical behavior of direct ink write structures, polymer microspheres are good candidates for shape memory elastomers requiring structural complexity, with potential applications toward tandem shape memory polymers.